305 CORRELATES OF CYTOTOXIC T-LYMPHOCYTE INDUCTION AT 1 AND 3 MONTHS OF AGE AMONG HIV-1 EXPOSED, UNINFECTED INFANTS. (1st January 2005) - Ashworth, M.; Redman, M.; Mbori-Ngacha, D.; Lohman, B.; John-Stewart, G.; Overbaugh, J.; Farquhar, C.
Abstract : Background: Transmission of human immunodeficiency virus (HIV) from mother to child occurs in utero, during delivery or during breastfeeding. Less than one-third of infants born to HIV-positive mothers become infected, however, and there is evidence that innate, humoral and cellular immune responses all contribute to protection in these infants. Several investigators have detected HIV-specific cytotoxic T-lymphocyte (CTL) induction in some HIV-negative infants exposed to HIV. Identifying correlates of this induction would both allow for better predictions of which mothers are most at risk for transmitting HIV to their offspring, and further our understanding of the transmission and pathogenesis of HIV. Methods: Pregnant, HIV-positive women were recruited through the "CTLs and Prevention of Breastmilk HIV Transmission" study. Their infants were serially assessed for HIV-1 DNA, HIV-1 RNA, and HIV-1-specific gamma-interferon-producing CD8+ cells. Infants that remained HIV-negative throughout the study period, and had Enzyme-Linked Immunosorbent Spot (ELISPOT) assays performed at month one, month three or both, were considered for the analysis (N=269). Our two end-points were positive ELISPOT assay at one and three months of age. Univariate analysis was performed using logistic regression, and for all tests, p ≤0.05 was used to determine a statistically significant association. Odds ratios and 95% confidence intervals were calculated for both continuous and categorical potential correlates. Results: Potential correlates relating to maternal health, deliveries, feeding practices, and infant health were considered. Mother's blood plasma log viral load at the time of delivery was associated with a lower odds of a positive infant CTL response at one month (OR=0.61 95% CI = 0.38-0.98 p = 0.041) and month three (OR = 0.56 95% CI = 0.34-0.94 p = 0.028). Conversely, breastmilk log viral load at one month post-partum was significantly associated with an increased odds of a positive infant CTL response at month three (OR = 2.0 95% CI = 1.2-3.3 p = 0.009). No significant relationships were found for the other potential correlates considered. Discussion: Our study suggests that the nature of the exposure to HIV, whether in blood plasma or breastmilk, may be an important determinant of whether an exposed, uninfected infant develops an HIV-specific CTL response. This may have relevance for development of vaccines that target cellular immunity against HIV.